TACE combined with sorafenib induces complete remission in an elderly patient with hepatocellular carcinoma, hepatic venous tumor thrombus, and diffuse lung metastasis: a case study and literature review - Guangsheng, Zhao; Song, Liu; Shunhang, Yin; Zhongyi, Ding; Shunxiong, Tang; Jun, Zhou; Yuewei, Zhang (Frontiers in Oncology, 2026)
Hepatocellular carcinoma (HCC) with hepatic venous tumor thrombus (HVTT) and synchronous lung metastases has a poor prognosis and limited treatment options. We present a 70-year-old male with chronic hepatitis B and BCLC stage C HCC, featuring a large liver tumor (14×12×10 cm), HVTT, and diffuse lung metastases. The patient was treated with transarterial gene embolization (TAGE) using gelatin sponge microparticles and rAd-p53 (Gendicine®), followed by sorafenib. Imaging showed rapid tumor necrosis at 4 days, significant reduction of lung nodules at 4 weeks, and complete tumor necrosis with resolution of lung metastases at 15 weeks. The patient achieved complete remission and remains alive with 14-year survival.